ĐÁNH GIÁ KHẢ NĂNG ỨC CHẾ ĂN MÒN ĐỒNG М-1 VÀ NHÔM АК-7 CỦA BENZOTRIAZOL TRONG DUNG DỊCH AXIT XITRIC 5% - Nguyễn, Thị Thu Xuân; Hoàng, Đức Quang; Vũ, Văn Huy; Nguyễn, Chí Cường; Nguyễn, Vân Anh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF CORROSION INHIBITION PROPERTIES OF BENZOTRIAZOLE ON COPPER M-1 AND ALUMINUM AK-7 IN 5%CITRIC ACID SOLUTIONThis paper presents the research results on the corrosion inhibition effect of benzotriazole on copper M-1 and aluminum AK-7 in 5% citric acid solution. Electrochemical test resultsshow that benzotriazole as a good corrosion inhibitors for copper M-1 and aluminum AK-7. The optimal protective concentration of benzotriazole in this condition is 0.5%, at which the protective effect for copper M-1 and aluminum AK-7 is 75.43% and 69.56% respectively. After 2 hours of corrosion test in glassware at 88±2°C by mass loss method with a concentration of 0.5% benzotriazole, the protective effect for copper M-1 and aluminum AK-7 reaches 69.1% and 65.4% respectively.